Հայ տարագիրները Սիրիայում Ֆեյսալ իբն Հուսեյնի իշխանության տարիներին (1918 թ. հոկտեմբեր – 1920 թ. հուլիս) - Նարինե Մարգարյան (ՀՀ ԳԱԱ հրատ.)
В годы осуществленного турецким правительством Геноцида армян депортированные армяне сталкивались с опасностью ассимиляции. Во время правления в Сирии короля Фейсала (1885–1933) депортированным армянам наряду с индивидуальной помощью предоставлялась также официальная. Помощь сирийских арабов армянам достигла своего апогея в 1919 году, когда были приняты специальные правительственные решения. Политика короля Фейсала по содействию национальным меньшинствам во многом способствовала улучшению положения армянских изгнанников. Депортированные aрмянe с помощью арабов не только пережили Геноцид, но и, преодолев трудности, превратились в полноправых граждан Сирии. In the years of the Armenian Genocide implemented by the Turkish Government, the Armenian deportees faced the constant threat of losing their national identity. During the rule of King Feysal (1885–1933) in Syria the assistance for deportees of individual character was implemented also through official channels. The Syrian Arab support peaked in 1919, when special governmental decisions were made on that issue. The Feysal policy to support national minorities fostered the assistance to Armenian deportees. One of the most essential decisions of Feysal was to return the Armenian children, women and girls to the Armenian environment, which gave a new impetus to the orphan collection activities in Syrian deserts. Another important step was the governmental decision to provide food and monthly allowances to the Armenian deportees. Feysal even met with Armenian political and spiritual leaders to discuss the issues related to the Armenian deportees. With the assistance of Arabs, Armenian deportees not only survived the Genocide but overcoming the difficulties transformed from deportees into full citizens.
Keywords: History; D History